Diagnostic performance of biomarkers for differentiating active tuberculosis from latent tuberculosis: a systematic review and Bayesian network meta-analysis - Jeong, Ji Hun; Shim, Sung Ryul; Han, Sangah; Hwang, Inhwan; Ihm, Chunhwa (Frontiers in Microbiology, 2024)
BackgroundPCR and culture tests are used together to confirm the diagnosis of active tuberculosis (TB). Due to the long culture period, if the PCR test is negative, it takes a significant amount of time for the culture result to be available. Interferon-γ release assays (IGRAs), which are widely used to diagnose TB or latent tuberculosis infection (LTBI), cannot effectively discriminate TB from LTBI. The purpose of this study is to analyze the diagnostic performance of various markers for differentiating between TB from LTBI.MethodsPubMed-Medline, EMBASE, Cochrane Library, and Web of Science were searched up to the end of May 2024, without restrictions on publication date and population. Articles describing the diagnostic value of at least one biomarker for differentiating between TB and LTBI were included. The QUADAS-2 tool was used to assess study quality. Two independent researchers assessed the articles using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The network meta-analysis (NMA) was performed for diagnostic tools of 11 groups used to differentiate TB from LTBI.ResultsOut of 164 identified articles, 159 reports were included in the systematic review and 58 in the meta-analysis. Seventy results from 58 reports accounting for 9,291 participants were included. When measuring interleukin-2 (IL-2) after stimulation with latency antigen, the most significant odds ratio was shown in terms of sensitivity, specificity, positive predictive value and negative predictive value. The values were 9.46, 18.5, 11.30, and 9.61, respectively.ConclusionThis study shows that the IL-2 level after stimulation with latent antigen is a potential biomarker for differentiating TB from LTBI.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024542996.